Mapping of Recurrence Sites Following Adjuvant or Salvage Radiotherapy for Prostate Cancer Patients - Gonzalez-Moya, Ana; Supiot, Stéphane; Seegers, Valérie; Lizée, Thibaut; Legouté, Florence; Perennec, Tanguy; Calais, Gilles (Frontiers in Oncology, 2022)
Introduction: Although salvage and adjuvant radiotherapy (RT) are effective in prostate cancer (PC) patients, 30-40% of men will have disease progression. The objective was to describe the pattern of recurrence in PC patients with biochemical failure (BF) following postoperative RT. Methods: We retrospectively analyzed 935 PC patients treated from 2009 to 2019 with adjuvant or salvage RT at Institut de Cancérologie de l’Ouest. Of these, 205 (22%) developed biochemical failure (BF) of whom 166 underwent imaging. Patients with identified radiologic failure prior any specific treatment were included to determine the site of relapse categorized as local (L)-only, locoregional (LR) or metastatic (M) recurrence. Main disease characteristics and RT fields were examined in relation to sites of recurrence. Results: 141 patients were identified with 244 sites of failure on imaging. Of these, 108 patients had received RT to the PB alone and 33 RT to the PB and pelvic lymph nodes (PB+PLN). Androgen-deprivation therapy was used concomitantly in 50 patients (35%). The median PSA at imaging was 1.6 ng/ml (range 0 – 86.7). In all, 74 patients (52%) had M disease (44% in the PB group and 79% in the PB+PLN group), 61 (43%) had LR failure (52% in the PB alone group and 15% in the PB+PLN group) and 6 (4%) had L-only failure, at a median of 26.7 (range 5 – 110.3) months from RT. Metastases were in extra-pelvic LN [37 (15%)], bones [66 (27%)] and visceral organs [8(3%)]. 53 (48%) of the pelvic LN failures in the PB group would have been encompassed by standard PLN RT volume. Conclusion: We found that most patients evaluated for BF after postoperative RT recurred outside the RT field. Isolated pelvic nodal failure was rare in those receiving RT to the PB+PLN but accounted for half of failures in those receiving PB alone RT. Imaging directed salvage treatment could be helpful to personalize radiation therapy plan.